On the triangular relationship between political corruption, gender inequality, and socio-economic development in Bangladesh - Ahmed, Ansar (© 2003 Bangladesh Development Initiative & The University Press Limited., 2017)
This book chapter was published in theDevelopment Issues of Bangladesh-II [© 2003 Bangladesh Development Initiative & The University Press Limited] and the book's detail available at: https://goo.gl/ba5CnB